Model Bisnis Klinik POLTRADA sebagai Fasilitas Kesehatan Tingkat Pertama (FKTP) Berbasis Blue Ocean Strategy (BOS) Wilayah Tabanan Bali: indonesia - Reinaldy Yuda Afriza; Sahat Saragi; Lies Putriana (PendIPA Journal of Science Education, 2025)
Poltrada Clinic is one of the First Level Health Facilities in Bali that serves 634 ‘BPJS Kesehatan’ participants. The clinic under the Ministry of Transportation has the opportunity to develop its services and business reach along with the development of the number of industries in Tabanan. Therefore, its performance needs to be evaluated to formulate an optimal business strategy. The analysis method uses SWOT analysis followed by the Quantitative Strategic Planning Matrix and Blue Ocean Strategy approaches to obtain the right strategic priorities and business models. Data collection was carried out by interviewing 8 informants. The results of the data analysis show: The SWOT matrix produces (x, y = 0.84; 1.89) where this point is in quadrant I, which means the clinic is in a favorable situation. Based on the CPM results from 7 key factors, Poltrada Clinic has a score of 3.49 which is in the first position compared to 3 existing clinics. This means that Poltrada Clinic has a stronger competitive advantage in various key factors for the success of the health service industry. The results of the QSPM matrix processing show that the highest value lies in alternative strategy 1, namely "Utilizing qualified facilities, existing human resources, complete health services, fast-accurate services and 24-hour services to attract cooperation with companies and transportation agencies in conducting basic MCU tests (S3, S4, S7, S8, S9, O3)". The strategy canvas shows a high offering value for each competency factor. Based on the blue ocean strategy, the Bali Poltrada Clinic must eliminate the inpatient room facility which is now an observation room to reduce operational costs. Reduce Operational costs due to excess human resources by maximizing the role of each profession. Raise ongoing digitalization, work motivation with performance-based incentives, and improve the clinic’s image through active promotion. Create basic MCU services, telemedicine services and collaborate with BPJS, companies including hotel/resorts, department of Transportation and physiotherapy. Poltrada Clinic is also advised to introduce a new tagline, namely: "Accurate examination, ready in 25 hours" which means accurate examination with the support of telemedicine technology, quality MCU services, and readiness more than just 24 hours for better health.